Load-specific variant generation of bead cross sections in sheet metal components by unidirectional carbon fibre reinforcement. Issue 1 (June 2021) - Ott, M; Haberkern, P; Gruber, M; Hartmann, C; Risch, T; Wunderling, C; Albers, A; Volk, W
Abstract: Beads are widely used to stiffen sheet metal components subjected to bending loads. Often, these bead-stiffened parts are used in product variants that differ significantly in the amount of acting loads. Lamination of unidirectional carbon fibre reinforced plastic (UD-CFRP) on the top flange area of individual beads represents a method for further increasing weight-specific stiffness: By varying the number of plies, a specifically configured component is obtained for each of the load cases. As a result, no changes to the forming tools are necessary and a minimum amount of the UD-CFRP material is required. In this work, a complete manufacturing process for a fibre reinforced bead was developed: First, a bead cross section geometry with an adapted top flange area to accommodate the UD-CFRP plies was designed and stamped into pre-stretched sheet samples of DX56 steel. Subsequently, the suitability of several surface pre-treatment processes to achieve sufficient bond strength of the composite bead was experimentally investigated and the UD-CFRP plies were applied by lamination. Final bending tests quantified the achievable stiffening effect of the investigated bead variants, showing a significant increase of the maximum supportable load compared to the standard non-reinforced cross-section.